Student Counseling Information System Design Web Based Using CodeIgniter Framework: Study at Senior High School Plus Al-Amanah - Luthfina Yulyanthika; Marjito Marjito; Ade Supriatna; Agung Tri Retnowaty; Farhanah Fitria M (Informatics Management, Engineering and Information System Journal, 2023)
The administrative process of counseling guidance services at SMP Plus Al-Amanah is still done manually which causes data collection of information on students still using books and filing in the BK room cupboard, counseling guidance at SMP Plus Al-Amanah is also still inputting and reporting achievements as well as violations by committing a private call sent via social media chat that specifically makes students have to go to school without holding an official letter from the BK when getting a call so that parents/guardians are worried and doubtful when the child is called to school if without written evidence. This results in physical exhaustion for both the guidance counselor and the students and creates doubt and concern for parents and guardians of students. To optimize time and distance, judging from these problems, a counseling guidance system was made using the OOAD model. The counseling guidance information system for SMP Plus Al-Amanah, can be used to manage the process of recording user data involved in the information system (administrators, operators, guests), recording violation and achievement data, recording student biodata, BK services, and calling students is a guidance process counseling that has been carried out. In addition, this information system can be used and viewed by parents via the Web so that counseling and data related to students can be monitored and viewed properly.